Isolated liver transplantation for treatment of liver failure secondary to intestinal failure - Spagnuolo Maria; Ruberto Eliana; Guarino Alfredo (BMC, 2009)
Abstract Intestinal Failure is a permanent loss of digestive and absorptive functions as a consequence of short bowel syndrome and/or other primary intestinal conditions. Patients with intestinal failure (IF) require long term parenteral nutrition to survive. The only alternative to parenteral nutrition is intestinal transplantation which still entails high mortality. Children with intestinal failure on parenteral nutrition may develop liver failure (LF), as a consequence of central line infections and other conditions. In children with both irreversible IF and LF a combined transplantation is generally considered. Despite low survival rate, combined liver/intestine transplantation is associated to better intestinal graft survival and lower incidence and severity of rejection compared to isolated small bowel transplantation. Recently, isolated liver transplantation was proposed in children with IF and LF. This procedure may have a higher survival probability compared to isolated intestinal transplant, it may allow progressive weaning from PN in children in whom the remnant intestine has the potential for adaptation and offer a timely solution in children for whom intestinal graft is not immediately available. This innovative approach may prove a better option compared to combined transplantation in both the short and long term